Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay-Two Stray Dalam Meningkatkan Hasil Belajar Akidah Akhlak Siswa Kelas VII MTsN 1 Pasaman Tahun Pelajaran 2019/2020 - Yogi Perkasa; Nazaruddin (Jurnal Al-Karim : Jurnal Pendidikan, Psikologi dan Studi Islam, 2020)
Learning activities are the main activities in the whole educationprocess. A good learning process is to involve students in the implementationof education. This means that the education process must be oriented tostudents (student center). Aqeedah moral subjects are considered students asone of the boring subjects. At MTsN 1 Pasaman, it is seen that the learning ofAqidah Akhlak is still centered on the teacher (Teacher center), while theschool has used the 2013 curriculum which should be a student-orientedlearning process (Student center). The lack of student activity in the learningprocess is due to the teacher's Aqidah Akhlak still using the lecture anddiscussion methods as well as the lack of variations in the use of models andlearning methods. The influence of the Two Stay-Two Stray type of Cooperativelearning model can improve the learning outcomes of moral code in VII gradestudents of MTsN 1 Pasaman. This researcher aims to find out the effect of theTwo Stay-Two Stray Cooperative learning model in improving the learningoutcomes of Morals in the VII grade students of MTsN 1 Pasaman. Thisresearch is a quasi experiment with a randomized control group only designresearch design. The subjects of this study were all Grade VII students ofMTsN 1 Pasaman in 2019/2020 Academic Year with a total of 9 classes. Datacollected in this study are student learning outcomes data, in cognitive aspects.Data were analyzed by the average two similarity test (T-test) by conducting anormality test and a homogeneity test. From the results of the T-test data the95% confidence level (α = 0.05) and dk = 62, then obtained tcount = 3.06>1.67 = ttable which means Hypothesis (H1) is accepted. The results of thestudy concluded that there was a significant influence of the Two Stay-TwoStray Cooperative learning model on the learning outcomes of the Morals ofthe VII grade students of MTsN 1 Pasaman 2019/2020 Academic Yearsignificantly. However, the authors also find several obstacles, namely in themanagement of classes that are less controlled, less effective time available.